Advancing Rapid Arsenic (III) Detection Through Device-Integrated Colorimetry - Sumalatha Bonthula (22155565) (2024)
It is essential to detect precise traces of inorganic arsenic ions when utilized, which may increase the risks of several health issues such as lung, bladder, skin cancer, and diabetes diseases. In this study, bromocresol green, chlorophenol red, and cresol red dyes were examined to detect the presence of arsenic (III). Further, we present a colorimetric arsenic (III) detection using a cost-effective paper-based sensor and portable device method. The calibration plot from UV-Vis absorption exhibited a detection limit of ∼0.054 µM of arsenic (III) in the detection range of 0–10 mM. The selectivity study establishes this method for visual on-site detection of arsenic (III) combined with the simultaneous presence of common coexisting ions. The paper and device-based dual strategy to detect arsenic (III) offered high sensitivity and selectivity under room conditions. Both the paper sensor and the proposed device have a potential for rapid on-site detection of arsenic (III). Therefore, it could provide a viable solution for the design of affordable, sensitive, and portable tools for the environmental monitoring of arsenic (III). Other Information Published in: Chemistry Africa License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s42250-024-01060-8